France since 1945 - Gildea, Robert, 1952- 1952- (Oxford Univ. Press, 1996)
The last fifty years have seen immense challenges for the French: constructing a new European order, building a modern economy, searching for a stable political system. It has also been a time of anxiety and doubt. The French have had to come to terms with the legacy of the German Occupation, the political and social implications of the influx of foreign immigrants, the destruction of traditional rural life, and the threat of Anglo American culture to French language and civilization